Geographical analysis of the effect of climate variables on comfort days in Darbandikhan district, by using Terjung classification (Raparin Journal of Humanities (RJH), 2024)
Climate has a direct impact on human health, comfort, and the execution of various activities, practical climate scientists are pay attention to the relationship between climate and humans. The aim of this study is to understand the climate types that have a direct impact on human comfort and to show the relationship between climate types and climate well-being in different time. To accomplish the objective of the study, the “Terjung " classification, which is a specific measure of a peaceful atmosphere, was employed. The study utilized records of climatic species in the Derbandikhan district between the years of 2002 and 2021. The study concluded that the impact of climate types varied according to the seasons and months of the year. The results showed that there were 48 calm days with a value of (0), accounting for a rate of (13.2%), and 58 calm nights with a value of (0), and accounting for a rate of (15.9%) throughout the year. Furthermore, the study found that the effect of calm and pleasant wind (-b) during the day was observed for 34 days, representing a rate of (9.3%), and at night, it was observed for 49 nights, accounting for a rate of (13.4%) throughout the year.